Arylpiperazine agonists of the serotonin 5-HT1A receptor preferentially activate cAMP signaling versus recruitment of β-arrestin-2. Issue 15 (1st August 2015) - Stroth, Nikolas; Niso, Mauro; Colabufo, Nicola A.; Perrone, Roberto; Svenningsson, Per; Lacivita, Enza; Leopoldo, Marcello
Graphical abstract: Abstract: G protein-coupled receptors (GPCRs) mediate biological signal transduction through complex molecular pathways. Therapeutic effects of GPCR-directed drugs are typically accompanied by unwanted side effects, owing in part to the parallel engagement of multiple signaling mechanisms. The discovery of drugs that are 'functionally selective' towards therapeutic effects, based on their selective control of cellular responses through a given GPCR, is thus a major goal in pharmacology today. In the present study, we show that several arylpiperazine ligands of the serotonin 5-HT1A receptor (5-HT1A R) preferentially activate 3′, 5′-cyclic adenosine monophosphate (cAMP) signaling versus β-arrestin-2 recruitment. The pharmacology of these compounds is thus qualitatively different from the endogenous agonist serotonin, indicating functional selectivity of 5-HT1A R-mediated response pathways. Preliminary evidence suggests that phosphorylation of extracellular signal-regulated kinases 1/2 (ERK1/2) downstream of 5-HT1A R is a substrate of functionally selective signaling by partial agonists. We propose that the compounds described in the present study are useful starting points for the development of signaling pathway-selective drugs targeting 5-HT1A R.